A Novel Orthotopic Transplant Methods of 3D Bio-Printed Assembly of Liver Bud. (July 2018) - Yanagi, Yusuke; Kobayashi, Eiji; Nakayama, Koichi; Enosawa, Shin; Taguchi, Tomoaki
Abstract : Introduction: The researches of liver regeneration using extracellular matrix, cell-sheet or liver organoid have progressed greatly in recent years. We previously reported a novel method of transplanting an in vitro-generated liver bud in the original place for hepatic organ in rat; orthoropic transplantation on the transected plane of liver (Yanagi Y et al. Scientific Reports. 2017). We here report new procedures of transplantation on the transected plane of liver in rat and porcine. Materials and Methods: Transplant method in rat: A liver lobe was fixed vertically with gauze. The hepatic capsule was cut by scissors, then the liver lobe was gradually ligated by 6-0 silk suture among the cut line. Liver parenchyma was transected and major vessels were ligated simultaneously to make a transected plane. The ligated tissue was carefully resected by scissors. The hepatic transplant materials were attached on the transected plane and the plane was covered by omentum. Transplant method in porcine: The hepatic capsule of a lobe was cut by an electric scalpel. Since the porcine liver lobe was thick, the liver parenchyma was transected by the clamp-crush technique. The isolated small vessels and bile ducts were cut by electric coagulation while pouring water on the transecting plane. Finally, the remained major vessels were ligated by absorbable suture and the hepatic transplant materials were attached on the transected plane. The plane was covered by omentum. We transplanted a fetal or 3D bio-printed liver bud with our methods. Results and Discussion: Our methods enabled to create the plane of intact liver parenchyma. Sever bleeding was not observed. The transplanted liver materials successfully engrafted on the liver. Our method may provide the essential environment of growing liver tissue through both portal and arterial blood flow. Conclusion: Although further studies are needed to investigate the better techniques and develop new devices for hepatic transection, our method is considered to be a promising approach of transplanting a 3D-engineered liver tissue for the regenerative therapy of liver.